2021
DOI: 10.1186/s13052-021-00969-x
|View full text |Cite|
|
Sign up to set email alerts
|

Incidental finding of APC deletion in a child: double trouble or double chance? – a case report

Abstract: Background 22q11.2 deletion syndrome is one of the most common genomic disorders, characterized by the variable presence of facial dysmorphisms, congenital cardiac defects, velopharyngeal insufficiency/cleft palate, thymic hypoplasia/aplasia, immunodeficiency, parathyroid hypoplasia, developmental delay, learning disabilities, psychiatric disorders, renal, ocular, and skeletal malformations, hearing loss and laryngeal abnormalities. Chromosomal microarray (CMA) hybridization is one of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In pathology, and specifically with respect to whole genome sequencing (WGS) or exome genome sequencing (WES) (analogous to a whole body scan in radiology), secondary findings occur with the detection of genetic variants throughout the genome or exome that are unrelated to the clinical indication for testing (Amendola et al, 2015). Secondary findings have also been reported with other types of comprehensive genetic and genomic applications including noninvasive prenatal testing (Bianchi et al, 2015;Mastromoro et al, 2021) and chromosomal microarray testing (Rosina et al, 2021). Although much of the literature has focused on secondary findings in the germline, it is also possible to detect secondary findings present in somatic tissues in germline testing due to mixed cell populations in the patient specimen (Weitzel et al, 2018;Chao et al, 2021).…”
Section: Pgx Secondary Findings Vs Other Secondary Findingsmentioning
confidence: 90%
“…In pathology, and specifically with respect to whole genome sequencing (WGS) or exome genome sequencing (WES) (analogous to a whole body scan in radiology), secondary findings occur with the detection of genetic variants throughout the genome or exome that are unrelated to the clinical indication for testing (Amendola et al, 2015). Secondary findings have also been reported with other types of comprehensive genetic and genomic applications including noninvasive prenatal testing (Bianchi et al, 2015;Mastromoro et al, 2021) and chromosomal microarray testing (Rosina et al, 2021). Although much of the literature has focused on secondary findings in the germline, it is also possible to detect secondary findings present in somatic tissues in germline testing due to mixed cell populations in the patient specimen (Weitzel et al, 2018;Chao et al, 2021).…”
Section: Pgx Secondary Findings Vs Other Secondary Findingsmentioning
confidence: 90%
“…Various extraintestinal manifestations, such as neoplasms of soft and hard tissue or the central nervous system, have been associated with FAP (Groen et al, 2008). In addition, several case reports have confirmed that children with pathogenic germline APC variants have a significant risk of developing HB (Alkhouri et al, 2010;Augustyn & Wallerstein, 2009;Cetta et al, 1997;Evers et al, 2012;Rosina et al, 2021;Sanders & Furman, 2006;Thomas et al, 2003). The main clinical characteristics as well as the prognosis of individuals with HB and FAP does not seem to differ from those of patients with sporadic HB (Trobaugh-Lotrario et al, 2018).…”
Section: Familial Adenomatous Polyposismentioning
confidence: 96%
“…However, it is currently unknown how the ECM environment of HGSOC differs from the normal ovarian environment and whether ECM modifications can offer diagnostic and therapeutic insights for this poor-prognosis cancer. Furthermore, it’s crucial to recognize that matrix components function not as isolated entities but as an interconnected network of matrix molecules [ 21 ]. Recent research has established the prognostic and predictive value of dysregulated stromal components in early non-small cell lung cancer [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%